1988
DOI: 10.1007/bf00930897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a televised smoking cessation intervention among low‐income and minority smokers

Abstract: In November 1985, a television smoking cessation program was broadcast for 20 days on the noon and 9 p.m. news. Smokers in West Garfield Park, an inner-city impoverished area of Chicago, were randomly assigned either to a comprehensive intervention or to a no-intervention control condition. Although 100,000 self-help manuals had been distributed throughout Chicago, none of the controls in this low-income area had obtained a manual. The intervention consisted of providing the smokers a self-help manual, the tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Our intervention was a relatively static audio-slide presentation. A more involving, compelling, and attentioneliciting media format such as a videotape might be even more effective (Jason, Tait, Goodman, Buckenberger, & Gruder, 1988). Future research dealing with this possibility, with regard to blood donations and other forms of prosocial behavior, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Our intervention was a relatively static audio-slide presentation. A more involving, compelling, and attentioneliciting media format such as a videotape might be even more effective (Jason, Tait, Goodman, Buckenberger, & Gruder, 1988). Future research dealing with this possibility, with regard to blood donations and other forms of prosocial behavior, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Our search identified 20 studies regarding the effectiveness of cessation series in increasing tobacco use cessation. 244,[252][253][254][255][256][257][258][259][260][261][262][263][264][265][266][267][268][269][270] Ten additional reports provide information on an alreadyincluded study. [271][272][273][274][275][276][277][278][279][280] Ten studies with limited execution 244,252,254,257,258,261,263,265,266,268 and one study with a least-suitable study design 255 were not included in the body of evidence.…”
Section: Mass Media Education: Cessation Seriesmentioning
confidence: 99%
“…[271][272][273][274][275][276][277][278][279][280] Ten studies with limited execution 244,252,254,257,258,261,263,265,266,268 and one study with a least-suitable study design 255 were not included in the body of evidence. Details of the nine qualifying studies 253,256,259,260,262,264,267,269,270 are provided at the website (www.thecommunityguide.org).…”
Section: Mass Media Education: Cessation Seriesmentioning
confidence: 99%
“…During this second project, WGN-Channel 9-a superstation whose programming is beamed via satellite throughout the United States and Central America-carried the 20-day program. For this program, 100,000 manuals were distributed through True Value Hardware stores (Jason, Tait, Goodman, Buckenberger, & Grader, 1988). Nielsen ratings conducted during the month the health promotion program was aired indicated that approximately 286,000 and 583,000 people in the Chicago area watched the noon and 9 p.m. broadcasts of the program, respectively.…”
Section: Smoking Cessation Interventionsmentioning
confidence: 99%